Human rights and internet access: Costa Rica and its challenges - Martén Saborío, Sergio (2021)
This paper develops a conception of human rights based on the institutional interpretation held by Pogge (2017) and Beitz (2009). This conception serves as a means to underpin an argument in favor of the legitimacy of internet access as a human right. Through an analysis of global and regional data, as well as data pertaining Costa Rica specifically, about internet access penetration and other factors that ought to be considered to make up a more detailed perspective, such as differences in access between developed, developing and least developed countries, along with differences in access in rural areas compared to urban areas, it is shown that the inclusion of internet as a human right has significative weight and effectiveness in practice.